Unilateral galactocele in a male infant - Vlahović, Aleksandar; Djuričić, Slaviša M.; Todorović, Sladjana (Vojnosanitetski pregled, 2015)
Introduction. Galactocele, generally occuring in young women during or after lactation, is an extremely rare cause of breast enlargement in infants and children of exclusively male gender. Only 26 cases have been published so far, including two our cases. Case report. We described unilateral, cystic, breast enlargement, without any endocrinologic and other abnormalities in a 29-month-old boy. A typical clinical and histopathologic presentation of galactocele was followed with a complete excision. Conclusion. This was a 27th well documented case of galactocele in a male infant with typical clinical and histopathologic presentation. There are several hypotheses regarding etiology of the lesion, but it is likely to be multifactorial. Because of its extreme rarity, there are some difficulties in differential diagnosis and treatment options of galactocele in male infants.